Hans Holbein, 1497/98-1543 - Buck, Stephanie, 1964-; Aston, Paul; Holbein, Hans, de Jongere, ca. 1497-1543; Murray, Chris (Cologne : Könemann, 1999)
Augsburg, Bazel en Luzerne - Thomas More - Engeland - Henry VIII - Chronologie
Translation from German, Paul Aston; editor of the English-language edition, Chris Murray.
Includes bibliographical references (p. 139).
Keywords: Holbein, Hans, -- 1497-1543 -- Criticism and interpretation